2020
DOI: 10.1007/s00018-020-03656-y
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 and CD14 trafficking and its influence on LPS-induced pro-inflammatory signaling

Abstract: Toll-like receptor (TLR) 4 belongs to the TLR family of receptors inducing pro-inflammatory responses to invading pathogens. TLR4 is activated by lipopolysaccharide (LPS, endotoxin) of Gram-negative bacteria and sequentially triggers two signaling cascades: the first one involving TIRAP and MyD88 adaptor proteins is induced in the plasma membrane, whereas the second engaging adaptor proteins TRAM and TRIF begins in early endosomes after endocytosis of the receptor. The LPS-induced internalization of TLR4 and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
544
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 805 publications
(571 citation statements)
references
References 268 publications
(486 reference statements)
15
544
0
12
Order By: Relevance
“…Toll-like receptor 4 (TLR4) is a transmembrane protein encoded by the TLR4 gene, which is involved in the innate immune response [16] , [17] , [18] . A number of studies have shown that LPS is the ligand of TLR4 and stimulates the inflammatory response of the lungs by binding to TLR4 [19] , [20] , [21] , [22] . It is now verified that TLR4-mediated mitogen-activated protein kinases (MAPKs) signaling pathways are responsible for the production of a variety of pro-inflammatory cytokines [23] , [24] , [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4) is a transmembrane protein encoded by the TLR4 gene, which is involved in the innate immune response [16] , [17] , [18] . A number of studies have shown that LPS is the ligand of TLR4 and stimulates the inflammatory response of the lungs by binding to TLR4 [19] , [20] , [21] , [22] . It is now verified that TLR4-mediated mitogen-activated protein kinases (MAPKs) signaling pathways are responsible for the production of a variety of pro-inflammatory cytokines [23] , [24] , [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, enhancers who had much higher signal in Low-dose were linked to genes like Csf1, Irf5, Rab11a, Ccr5, Irf7, Ticam2, Ifit3, and Irf1, while enhancers with lower signal in Low-dose were linked to genes like Arg1, Hdac5, and Treml1. Rab11a is responsible for transporting TLR4 from the endocytic recycling compartment to forming phagosomes 37 . This transport triggers the TRIF-dependent signalling pathway, which requires TRAM (Ticam2).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, both pathways are involved in the canonical activation of the NRLP3 inflammasome, which is responsible for the activation of the inflammatory cytokine, IL-1ÎČ, and can cause pyroptosis, a form of programmed cell-death 37 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several Gram-negative bacteria, including Actinobacillus pleuropneumoniae and Haemophilus parasuis, are responsible for respiratory diseases and cause huge economic losses to the swine industry worldwide. Lipopolysaccharide (LPS) is a cell outer membrane component of Gram-negative bacteria and serves as a major pro-inflammatory stimulus binding to pattern recognition receptor Toll-like receptor 4 (TLR4) (Ciesielska et al, 2020). LPS is ubiquitous in nature and exists in high concentrations in air pollution, soil, and organic dust.…”
Section: Introductionmentioning
confidence: 99%